Commitment, creativity and brains: Perspectives on gifted education - Rigo, Daiana Yamila (2020)
This chapter presents three current perspectives that come together to think about the educational practices of gifted children. The theoretical advances regarding commitment, creativity and the brain are discussed, lines of research that show the importance of promoting the configuration of instructional contexts that highlight differences in ways of learning, respecting 238the times and styles of each person, from the socio-constructivist perspective. From a sociocultural approach, arguments are put forward for understanding that giftedness is the result of the joint interaction of multiple contextual and personal factors, resulting in the value of practices found in the model of the three rings.